Pengembangan Dan Evaluasi Sediaan Farmasi Baru: Tinjauan Literatur - Najmah Salsabila; Rifqi Ferry Balfas (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
The development of new pharmaceutical preparations is a crucial process in the pharmaceutical industry to improve the effectiveness, safety, and convenience of drug use. Innovation in pharmaceutical preparations focuses not only on the discovery of new active substances but also on the development of improved drug delivery systems, dosage forms, and formulation technologies. This article aims to systematically review the stages of development and evaluation of new pharmaceutical preparations based on national and international literature. The method used is a literature review of scientific journals, pharmaceutical textbooks, and official guidelines. The review results indicate that the development of new pharmaceutical preparations involves pre-formulation, formulation, stability testing, and physicochemical and biopharmaceutical quality evaluation. Comprehensive evaluation is necessary to ensure the quality, safety, and effectiveness of the preparation before its production and widespread use.